Sex Differences in Body Ownership in Adults With Autism Spectrum Disorder - Guerra, Silvia; Spoto, Andrea; Castiello, Umberto; Parma, Valentina (Frontiers in Psychology, 2019)
A strong male prevalence has been observed in autism spectrum disorder (ASD) since its definition, but the behavioral manifestations of sex disparity have yet to be clarified. Here, we investigate sex differences in the perception of the Numbness Illusion (NI), a procedure based on a tactile conflict, in adults with ASD and with typical development. We aim to assess if women and men with ASD perceive NI-dependent body ownership differently and whether sex differences emerge in individuals with typical development. To elicit the NI, participants pressed their right-hand palm against the confederate’s hand and stroked with the thumb and the index finger of their left hand the joined index fingers in a synchronous or asynchronous way. Results reveal that women with ASD present a reversed and atypical pattern for the NI compared to men with ASD and a group of matched controls. In particular, women with ASD report a stronger illusion than men with ASD, that is more evident in the asynchronous conditions. In the asynchronous condition, women in the ASD group report stronger NI as compared to women and men in the Control group, whereas men with ASD only to men in the Control group. In the typical sample, the NI emerges only in the synchronous condition and no sex difference is observed. We discuss our results in terms of potential advantage of women in sociality and sensory information processing that might lead women with ASD to use different modalities to solve the illusion compared to men with ASD. In sum, these outcomes describe sex differences in individuals with ASD in the domain of illusory perception. This may be used in the future to support the characterization of the female phenotype of autism.